CLUSTERING DATA KENAIKAN KELAS SISWA MADRASAH TSANAWIYAH (MTs) MENGGUNAKAN METODE FUZZY C-MEANS ( STUDI KASUS MTs PLUS AL AMIN BANJAREJO ) - Joko Nurkholis; Kresna Oktafianto; Hamim Thohari (MathVisioN, 2022)
Grade promotion is an annual routine activity for a school at the elementary, junior high and high school levels. This activity becomes a problem when the class increase will be grouped into two classes. The process of selecting students to fill classes with superior categories and ordinary classes by looking at the number of student competency scores. This study, it is used to explore student competencies which are arranged in report cards when grades increase. With the Fuzzy C-Means algorithm, various competencies of prospective students can be grouped in detail according to the competencies that students have. The results of this clustering will be the basis for placing prospective students into superior or ordinary classes. By forming a community of superior classes and ordinary classes, there is a new climate for learning strategies and methods that are expected to make the learning process comfortable, fun and competitive. Cluster evaluation is carried out with the proximity of students' competencies in a cluster which shows the difference in quality between the superior class and ordinary class clusters. Cluster evaluation based on PCI index (Partition Coefficient) = 0.7675966 (Strong).